Authentic Though Not Exotic: Essays on Filipino Identity - Zialcita, Fernando N (Archīum Ateneo, 2006)
Suggests that through a dialectical process, the encounter between the Western and the indigenous has generated a broader sense of community that has transcended the kin. Local genius transformed Spanish influences, even as it was itself transformed by the latter, resulting in a new culture.